MODIFIKASI GEBOTAN BERORIENTASI ERGONOMI MENINGKATKAN KINERJA PETANI WANITA PERONTOK PADI DI SUBAK MARGAYA DESA PEMECUTAN KELOD KODYA DENPASAR - Rasna, I Made; Tirtayasa, Ketut; Sutajaya, I Made (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2015)
During threshing rice activity, farmers in forward banding. This posture caused musculoskeletal disorders, fatigue, workload, and that all can reduce work productivity. Therefore, to overcome these problems it can be done with using ergonomics oriented gebotan modification, by adjusting gebotan’s height relatedto farmer’s anthropometry. The aims of this study to determine the  farmers’ performance improvement  that can be  seen from the  decrease  of  farmers'workload,  fatigue,  and  musculoskeletal disoders  as well as  an increase inproductivity after using the  modification of gebotan.This experimental study using treatment by subjects design, carried out on15 female farmers rice thresher of Subak Margaya. Musculoskeletal disorderswere collected by Nordic Body Map questionnaire, the workload is determinedbased on the increase in work heart rate. Heart rate prequency was measured by ten pulse method, fatigue was recorded by a 30 item of ratting scale questionnaire, and productivity was recorded by the amount of grains which threshed  in certain time. Data analysis was using t-paired test with a significant level of 5%.Before the  intervention  the  musculoskeletal disorders  score was 78.15;fatigue 73.95, work pulse 37.761, and productivity  0.645 respectively. With the score ergonomics oriented gebotan modification, the score of musculoskeletal disorders can be reduced to 43.35, fatigue 52.82, and work pulse 22,945, andproductivity increased to 1.19. The decrease of  musculoskeletal disorders 44.53%  (p <0.05), reduce of fatigue 28.57% (p <0.05), reduce workload 42.3% (p <0.05) and increasing productivity 83%  (p <0.05).The conclusions of this study, the ergonomics oriented gebotan modificationcan reduce  musculoskeletal disorders,  fatigue,  workload,  and  increase theproductivity of farmers. To farmers who threshing using gebotan recommended to, adjust the gebotan’s height as high as the user’s grip so in the process of threshing, the farmers working in physiological standing stance
Keywords: Modified gebotan, ergonomics, performance and farmers threshing rice